Preferences and Evaluations of Spanish-Speaking University Students on Chinese Language Textbooks - Jia, Lin (Sinología hispánica. China Studies Review, 2026)
In Spain, in 2018, the number of Spanish students learning Chinese surpassed 40,000, and an increasing number of universities offer Mandarin Chinese courses at both undergraduate and master's levels. This growth has also sparked significant interest in the use and development of Chinese language teaching manuals in the academic field. The New Practical Chinese Reader, being the most widely used manual in Spanish universities for over 20 years, has been an exemplary and excellent guide to the Chinese language; however, its utility in certain aspects of language teaching does not align with current times. Therefore, this study conducted a questionnaire aimed at 68 Spanish university students majoring in Mandarin Chinese as their first foreign language, in order to understand their preferences, opinions, and evaluations of the New Practical Chinese Reader. The results obtained provide a foundation for the creation of future Chinese teaching manuals and the application of advanced teaching methods.